Accounting for cross-country differences in intergenerational earnings persistence: The impact of taxation and public education expenditure - Hans A. Holter (Quantitative Economics, 2015)
I document a strong negative cross-country correlation between intergenerational earnings persistence and measures of tax progressivity and level, and between intergenerational earnings persistence and public expenditure on tertiary education. To explain these correlations, I then develop an intergenerational life-cycle model of human capital accumulation and earnings that features progressive taxation, public education expenditure, and borrowing constraints among the determinants of earnings persistence. I calibrate the model to U.S. data and use it to decompose the contributions to earnings persistence from different model elements and to quantify how earnings persistence in the United States changes as I introduce tax and education expenditure policies from other countries. I find that individual investments in human capital account for 73% of the estimated intergenerational earnings persistence in the United States. Taxation, through its impact on investments in human capital, can explain 50% of the variation between the United States and 10 other countries, whereas borrowing constraints, which have received much attention in the literature, have a limited impact on earnings persistence.
Keywords: 330; Intergenerational earnings persistence; taxation; public education expenditure